Beyond Transactions: Exploring Employee-Customer Interaction in Retail Persuasion Scene - Pageyasa, Wayan; Sarmadan, Sarmadan (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
This study investigates the role of persuasive communication in shaping customer behavior within retail environments, focusing on in-store interactions between customers and retail employees. Using a qualitative approach, we employed discourse analysis to examine the verbal and non-verbal communication strategies that influence customer decision-making and purchasing behavior. Data were collected from several retail locations across Indonesia, involving in-depth observations and recordings of employee-customer exchanges. The study highlights key persuasive techniques, including the use of urgency, social proof, and personalized recommendations, all of which were found to significantly affect customer engagement, perceived value, and purchase intent. Specifically, the findings reveal that communication strategies that align with customer interests and build a sense of urgency were most effective in encouraging immediate purchases. Moreover, the study identifies contextual factors, such as cultural nuances and the role of trust in the Indonesian retail context, that mediate the effectiveness of these persuasive techniques. These findings contribute to the broader understanding of how persuasion operates in retail settings, particularly in non-Western cultures. The research also has practical implications, suggesting that retail managers can enhance customer engagement and boost sales by training employees in specific communication strategies that foster trust and urgency. This study provides valuable insights into how persuasive communication can be optimized to influence consumer behavior and improve retail outcomes.